The American dream : pop to the present - Coppel, Stephen; Tallman, Susan; Daunt, Catherine; Seligman, Isabel; Ramkalawon, Jennifer; British Museum (London : Thames and Hudson, 2017)
The American Dream: From Pop to present presents an overview of the development of American printmaking since 1960, paying particular attention to key figures such as Jasper Johns, Robert Rauschenberg and Andy Warhol. The 1960s was a period of change in the production, marketing and consumption of prints and the medium attracted a new generation of artists whose attitude towards making art had been conditioned by the monumentality and bold, eye-catching nature of popular imagery in postwar America, from advertising billboards to drive-in movies. Artists used to working on large canvases and huge sculptures created prints of an unprecedented ambition, scale and boldness in state-of-the-art workshops newly established on both the East and West coasts. Prints also became a means for expressing opinions on the great social issues of the day, from civil rights to the overt and covert role of government. This has continued, with feminism, gender, the body, race and identity, all topics represented in prints in a variety of stylistic approaches across the decades. The changing nature of American society provides a core element of the narrative, with prints offering a fascinating insight into contemporary thinking and attitudes.
Piecing together the American dream / Stephen Coppel -- Irresistible: the rise of the American print workshop / Susan Tallman -- 1. Pop art -- 2. Three giants of printmaking: Johns, Rauschenberg, Dine -- 3. The print workshop: Laboratories of experimentation and collaboration -- 4. Made in California: the West Coast experience -- 5. Persistence of abstraction: gestural and hard-edge 1960s-1970s -- 6. Minimalism and conceptualism from the 1970s -- 7. Photorealism: portraits and landscapes -- 8. The figure reasserted -- 9. Politics and dissent -- 10. Feminism, gender and the body -- 11. Race and identity: unresolved histories -- 12. Signs of the times.
"This publication accompanies the exhibition 'The American Dream: pop to the present' at the British Museum from 9 March to 18 June 2017"--Title page verso.
Includes bibliographical references (pages 321-325) and index.
Keywords: Johns, Jasper, -- 1930- -- Exhibitions; Dine, Jim, -- 1935- -- Exhibitions; Rauschenberg, Robert, -- 1925-2008 -- Exhibitions; Warhol, Andy, -- 1928-1987 -- Exhibitions; Prints, American -- 20th century -- Exhibitions; Prints -- Technique -- History -- 20th century -- Exhibitions; Prints -- Social aspects -- United States -- Exhibitions; United States -- Social life and customs -- 20th century